Surgical Outcome of Giant Vestibular Schwannomas: A Retrospective Analysis - Mohamed I. Refaat; Omar Y. Abdallah (Indian Journal of Neurosurgery)
Background Giant vestibular schwannomas, more than 4.5 cm in diameter, are still representing the majority of vestibular schwannomas in developing countries. The philosophy of incomplete and intracapsular tumor excision has been introduced in the management of these giant tumors, balancing the long-term tumor control and postoperative clinical outcome. Objective The aim was to review the cases with giant vestibular schwannomas and studying their prevalence, morbidity, and mortality rates. Patients and Methods This study was conducted retrospectively on data of patients who had undergone microsurgical excision of vestibular schwannomas in our institute between January and December 2017. The functional outcome of the patients was assessed by comparing the preoperative and the postoperative neurological examination, as well as the Karnofsky performance score. Results Twenty-two cases with vestibular schwannomas were included in this study. Among these 22 cases, 15 cases had giant vestibular schwannomas (68.2%). The tumors’ largest extracanalicular diameters ranged from 4.5 cm to 6.2 cm. Postoperative images showed gross total excision of the tumor in 11 cases (73.3%), and subtotal excisions in four cases (26.7%). Twelve cases (80%) had postoperative facial palsy. We encountered no mortality in our cases and three cases (20%) were symptom-free postoperatively (apart from hearing affection). Conclusion Large and giant vestibular schwannomas are still commonly met in neurosurgical practice in developing countries; they have different behaviors and presentations from those of smaller tumors. Both patient and surgeon expectations from surgery should be toward no mortality and mild or no morbidities.